An obstacle clearance test for evaluating sensorimotor control after anterior cruciate ligament injury: A kinematic analysis. Issue 1 (11th March 2021) - Grinberg, Adam; Strong, Andrew; Buck, Sebastian; Selling, Jonas; Häger, Charlotte K.
Abstract: Sensorimotor deficits, particularly proprioceptive, are often reported following rupture of the anterior cruciate ligament (ACL). High secondary injury rates and long‐term negative consequences suggest that these deficits are not properly identified using current assessment methods. We explored a novel obstacle clearance test to evaluate sensorimotor control in individuals following ACL reconstruction (ACLR) and rehabilitation. Thirty‐seven post‐ACLR individuals, 23 nonathletic asymptomatic controls (CTRL), and 18 elite athletes stepped over a hurdle‐shaped obstacle, downward vision occluded, aiming for minimal clearance. Kinematic outcomes (3D motion capture) for the leading and trailing legs, for two unpredictably presented obstacle heights, were categorized into Accuracy: vertical foot clearance and minimal distance from the obstacle; Variability: end‐point and hip/knee trajectory; and Symmetry: trunk/hip/knee crossing angles, hip–knee–ankle movement, and velocity curves. Accuracy was worse for CTRL compared with both other groups. ACLR had less leading and trailing vertical foot clearance with their injured compared with their noninjured leg. ACLR and athletes had less crossing knee flexion in their injured/nondominant legs compared with their contralateral leg, both leading and trailing. ACLR showed greater trunk flexion when crossing with their injured leg, both leading and trailing. For the leading leg, ACLR showed greater asymmetry for the hip–knee–ankle velocity curve compared with elite athletes. Trailing leg trajectory variability was lower for ACLR compared with CTRL and athletes for higher obstacles. Clinical significance: Sensorimotor deficits in individuals post‐ACLR were reflected by greater asymmetry and less variable (more stereotypical) trajectories rather than limb positioning ability. This consideration should be addressed in clinical evaluations.